A rare case of non-neutropaenic typhlitis in immunocompetent patient – case report - Mustapar, Nurulhasanah; Jaafar, Hasnan; Yahya, Maya Mazuwin; Mohamed, Khairun Nisa (Malaysian Journal of Pathology, 2017)
Introduction: Typhlitis is necrotizing inflammation of the caecum manifested by febrile right lower quadrant abdominal pain. All cases in literature have been described in immunocompromised such patients with neutropenia, haematological or solid malignancies, and following immunosuppressive therapy. We believe this case represents an example of typhlitis in non-immunocompromised patient, among the first such case reported. Clinical case: We would like to highlight a case of a 49-year-old Malay lady, with unremarkable clinical background. She initially presented with sudden onset of progressively worsening right lower abdominal pain associated with high grade fever and tachycardia. Abdominal examinations revealed a palpable mass and localised tenderness in the right iliac fossa. Blood investigations showed leucocytosis without any significant neutropenia. Ultrasound showed thickening of surrounding mesenteric fat with an irregular tip appendicolith suggested a diagnosis of perforated appendix. Intraoperatively, revealed an inflammed pre-ileal appendix and perforated caecum 3cm from the base of the appendix. Her post-operative recovery was uneventful. Pathological findings: Gross examinations of the specimen showed an acutely inflammed appendix with a suspicious area of perforation noted at the caecum measuring 10mm with surrounding ischaemic areas covered with slough and grossly oedematous. Histopathologically, there is acute appendicitis with acute perforated caecitis or otherwise known as typhlitis. Conclusion: Typhlitis may present in immunocompetent patients and should be considered in the differential diagnosis of patients exhibiting febrile right lower quadrant abdominal distress. Early and appropriate diagnosis allows management at an early stage and prevents complications and mortality.